Vital Conversations : Improving Communication Between Doctors and Patients. - Rosen, Dennis (Columbia University Press, 2014)
The health-care system in the United States is by far the most expensive in the world, yet its outcomes are decidedly mediocre in comparison with those of other countries. Poor communication between doctors and patients, Dennis Rosen argues, is at the heart of this disparity, a pervasive problem that damages the well-being of the patient and the integrity of the health-care system and society. Drawing upon research in biomedicine, sociology, and anthropology and integrating personal stories from his medical practice in three different countries (and as a patient), Rosen shows how important good communication between physicians and patients is to high-quality--and less-expensive--care. Without it, treatment adherence and preventive services decline, and the rates of medical complications, hospital readmissions, and unnecessary testing and procedures rise. Rosen illustrates the consequences of these problems from both the caregiver and patient perspectives and explores the socioeconomic and cultural factors that cause important information to be literally lost in translation. He concludes with a prescriptive chapter aimed at building the cultural competencies and communication skills necessary for higher-quality, less-expensive care, making it more satisfying for all involved.